The Assessment of Presenteeism and Activity Impairment in Behcet's Syndrome and Recurrent Aphthous Stomatitis: A multicentre Study - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN; BEYHAN, TUĞBA EMİNE (My University, 2021)
OBJECTIVE: To evaluate key factors for Presenteeism and Activity impairment in multinational patients with Behçet's syndrome (BS) and recurrent aphthous stomatitis (RAS). METHODS: In this cross-sectional study, 364 BS patients from Jordan, Brazil, the United Kingdom and Turkey and 143 RAS patients from the United Kingdom and Turkey were included. Work Productivity Activity Impairment (WPAI) scale was used for Presenteeism and Activity impairment. Mediation analyses were performed to evaluate both direct and indirect causal effects. RESULTS: Presenteeism score was higher in active patients with genital ulcers and eye involvement as well as patients with comorbidities and current smokers than the others in BS (p< 0.05). In RAS, Presenteeism score was elevated by oral ulcer activity in the direct path (p= 0.0073) and long disease duration as a mediator in the indirect path (p= 0.0191).Patients with active joint involvement had poor scores in Absenteeism, Presenteeism, Overall impairment and Activity impairment compared with those of inactive patients (p < 0.05). Using mediation analysis, the Activity impairment score was directly mediated by joint activity (p = 0.0001) and indirectly mediated through oral ulcer-related pain in BS (p = 0.0309). CONCLUSION: In BS, Presenteeism was associated with disease activity, presence of comorbidities and being a current smoker, whereas in RAS, Presenteeism was associated with oral ulcer activity and increased length of the disease. Moreover, Activity impairment was adversely affected by joint activity and oral ulcer related pain in BS. Patients need to be empowered by using appropriate treatment strategies in their working environment and daily life.
Keywords: Behçet’s syndrome; Mediation analysis; Aphthous stomatitis; Daily activity; Presenteeism